UMP Chancellor called on efforts to strengthen the culture of integrity and happiness in the education system - UMP, PNC (2018)
Universiti Malaysia Pahang (UMP) Chancellor, His Royal Highness Regent of Pahang Tengku Mahkota Tengku Abdullah Al-Haj Ibni Sultan Haji Ahmad Shah Al-Musta’in Billah called on for some strategic adjustments that emphasised on the transparency aspect in governance based on integrity, accountability and ethics.